Risks and occurrences of adverse events in the perception of health care nurses - Robson Tostes Amaral; Ana Lúcia Queiroz Bezerra; Cristiane Chagas Teixeira; Thatianny Tanferri de Brito Paranaguá; Thaisa Cristina Afonso; Adrielle Cristina Silva Souza (Universidade Federal do Ceará, 2019)
Objective: to analyze the risks and occurrences of adverse events in hospitalized patients from the perspective of nurses. Methods: cross-sectional study, developed with 41 nurses. We used a self-administered instrument titled Adverse Events Associated with Nursing Practices validated in Portugal and adapted to the Brazilian reality. Results: the amount of employment bonds (p=0,019) and weekly workload (p=0.002) foster failures in care assistance. There was a positive correlation between pressure and falls injuries (p<0.001), medication errors and pressure injuries (p=0.004) and infections related to health care and medication errors (p=0.006). Conclusion: the analysis showed that the occurrence of adverse events in care such as pressure injuries and infections related to health care were the most frequent in the perception of nurses. Drug errors had the lowest incidence among the results of the explored domains.